Patterns and reliability of children's skin temperature prior to and during sleep in the home setting - McCabe, S.; Elliott, Catherine; Langdon, K.; Abbiss, C. (Elsevier Inc., 2018)
© 2018 Elsevier Inc. The relationship between patterns of change in skin temperature and sleep is well recognized. In particular, there is a rapid rise in distal skin temperature (Tdistal) and slower rise in proximal skin temperature (Tproximal) prior to sleep onset. The difference between Tdistaland Tproximalis known as the distal-proximal gradient (DPG). Rise in DPG is known as a measure of distal vasodilation, which contributes to the drop in core body temperature (Tcore) that is important to sleep onset and maintenance. Patterns of change in skin temperature before and during sleep are reported for neonates, infants, adults and elderly, however they are not known for school aged children. Therefore, the current observational study aimed to determine the patterns and reliability of skin temperatures (Tskin) and DPG in relation to sleep of school aged children in their home settings. Participants (22 children, aged 6–12) completed the Children's Sleep Habits Questionnaire and used Thermochron iButtons and actigraphy for four school nights in their typical sleep settings. There were evident patterns of Tskinchange before and during sleep. In particular, Tdistalwas lower but rose more rapidly than Tproximalafter reported bedtime and prior to sleep onset. This reflected a timely rise in DPG, and shows that distal vasodilation precedes sleep onset in school aged children. The measures of Tskinand sleep were practical for children in their home settings, and the observed patterns were consistent across consecutive school nights. Environmental and behavioural strategies that manage skin temperature before and during sleep should be explored for their potential as valuable components of treatment of childhood insomnia.